Pengembangan Media Gambar Untuk Penyuluhan Agama Kristen Bagi Anak Usia Dini di PAUD KB ANANDA Kecamatan Sipoholon Kabupaten Tapanuli Utara - Winda Manalu; Goklas J Manalu; Regina B.M Nainggolan; Damayanti Nababan; Melina Agustina Sipahutar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to develop image media as a tool for Christian religious education that can be applied to early childhood education activities. This study uses a research and development (R&D) method by implementing ADDIE which is limited to three stages due to time and material limitations. The data collection technique uses a questionnaire that is evaluated by media experts, linguists, and early childhood experts. Aspects of assessment by linguists include the suitability of the language to the child's age, clarity of language, readability and fluency, as well as the appropriateness of spelling and punctuation. The assessment results showed an average feasibility with a percentage reaching 93.25% and the category "very feasible". Then the assessment aspects by media experts include visual appeal, clarity and simplicity, relevance and representation and increasing understanding. The assessment results showed an average feasibility with a percentage reaching 100% and the category "very feasible". Meanwhile, the assessment aspects by early childhood experts included content and language, visuals and appearance as well as readability and fluency. The assessment results showed an average feasibility with a percentage reaching 93% and the category "very feasible". Product validation identified that image media is very suitable for use as a tool in religious counseling activities for early childhood. This study provides an important contribution in the development of media that is appropriate to the needs and characteristics of early childhood, as well as providing strong recommendations for the implementation of image media for early childhood in PAUD KB ANANDA.